PARADIGMA ANTROPOSENTRIS DALAM MEMAHAMI HADIS-HADIS MUAMALAH - Salamah Noorhidayati (Jurnal Theologia, 2017)
Abstract: In this contents, Hadith reflects the different teaching of Islam, including creed, worship, and muamalah. All of that requires a different treatment and understanding the proportionally. This article examines how to understand the Hadiths in the field of muamalah and what is the paradigm construct of it. By using the method of subjective-humanistic hermeneutics, this article produces findings, as follows: first, the Hadiths of muamalah reflect construct of human relationships and it can change according to the changes and development of social life. Therefore, these Hadiths can be understood by using the anthropocentric paradigm, oriented on the needs of humans and make it as a subject and object either of the understanding. Second, this anthropocentric paradigm aims to find the sunnah and host it again in the present day. This anthropocentric understanding holds on to the principles and the universal values contained in the text of the Hadith as well as humanistic social ethics that upholds human values that are fairness, equal and tolerant without discrimination in various fields.Abstrak: Dari segi kandungannya, hadis Nabi mencerminkan muatan ajaran tentang akidah, ibadah dan muamalah. Kesemuanya itu membutuhkan pensikapan yang berbeda dan pemahaman yang proporsional. Artikel ini mengkaji bagaimana memahami hadis-hadis Nabi dalam bidang muamalah serta bagaimana konstruksi paradigma yang dimaksud. Dengan menggunakan metode hermeneutika subjektif-humanistik, artikel ini menghasilkan temuan, sebagai berikut: Pertama, hadis muamalah merefleksikan konstruk relasi manusia, dan bisa berubah sesuai dengan perubahan dan perkembangan kehidupan sosial. Oleh karena itu hadis-hadis ini bisa dipahami dengan menggunakan paradigma antroposentris, yang berorientasi pada kebutuhan manusia dan menjadikannya sebagai subjek sekaligus objek dalam pemahaman. Kedua, paradigma antroposentris ini bertujuan untuk menemukan sunnah Nabi dan menghadirkannya kembali dalam konteks sekarang. Pemahaman antroposentris ini berpegang pada prinsip dan nilai-nilai universal yang terkandung dalam teks hadis serta etika sosial humanistik yang menjunjung tinggi nilai kemanusiaan yang berkeadilan, setara dan toleran tanpa diskriminasi dalam berbagai bidang.